Retrospective Study of Basal Cell Carcinoma and Related with Different Parameters in Ghazy Al-hariri Hospital for Surgical Specialist - Abdulhussain, Mustafa Mohammed (Diyala Journal of Medicine, 2019)
Background: Basal Cell Carcinoma is a malignant epithelial neoplasm of the skin that can be seen in the area of chronic sun exposure. If it is inadequately treated or left untreated, it can cause local tissue invasion and low death. Objective: To evaluate different parameters of basal cell carcinoma cases referred to Ghazy Al-hariri Hospital for Surgical Specialist. Patients and Methods: Retrospective study done in Ghazy Al-hariri hospital for surgical specialist, medical city, Baghdad during the period from 2009 till 2012, 6579 reports from archives of histopathological laboratories were review of malignant cases,84 cases of Basal cell carcinoma, 54 were men and 30 were women. Confirmatory histopathological re-evaluation of some or incomplete information was done, full information has been taken directly from report and the information was arranged in an informative formula sheet which includes, age, gender, anatomical site of tumor, tumor type and tumor size. Results: In this study the percentage of basal cell carcinoma in relation to the total number is (1.3%), the results showed that 54 (64.3%) were men and 30 (35.7%) were women and the mean age of these patients was (69.9) years. Among basal cell carcinoma lesions, 28 cases were pigmented type, 18 cases were nodular type, 14 cases were ulcerated type, 10 cases were plaque type, 9 cases were basosqumous type and 5 cases were unclear. Conclusion: The present study revealed significant differences in age between male and female, also most basal cell carcinoma lesions were located on the head and neck area.